2011
DOI: 10.1590/s1982-56762011000600002
|View full text |Cite
|
Sign up to set email alerts
|

Powdery scab effect on the potato Solanum tuberosum ssp.andigena growth and yield: andigena

Abstract: Powdery scab affects most potato production zones in the world. The causal organism Spongospora subterranea f. sp. subterranea forms galls in roots and lesions on tubers during its replication. Recent researches suggest that S. subterranea could cause harmful effects on the host plant and potentially on yield. In order to quantify the disease impact on plant growth and yield, potato Solanum tuberosum ssp. andigena, cv. Diacol Capiro was grown in a soil infested with S. subterranea and compared to a healthy con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 22 publications
0
6
0
1
Order By: Relevance
“…Gilchrist et al . () demonstrated, also in a pot experiment, that height, shoot dry weight and tuber weight of S. tuberosum subsp. andigena plants were reduced in S. subterranea ‐infested soil, relative to pathogen‐free soil.…”
Section: Introductionmentioning
confidence: 82%
“…Gilchrist et al . () demonstrated, also in a pot experiment, that height, shoot dry weight and tuber weight of S. tuberosum subsp. andigena plants were reduced in S. subterranea ‐infested soil, relative to pathogen‐free soil.…”
Section: Introductionmentioning
confidence: 82%
“…andigena , and S. phureja , we found no evidence of genetic differences in Sss related to different hosts in either the sequence-based phylogeny reconstruction or in the microsatellite based cluster analysis. On Colombian potatoes, tuber lesion formation is rare [22]; for that reason, tuber lesion samples have been obtained from only one region in Colombia. However, we do not think that this sampling introduced a bias caused, for example, by regional adaptation, since F ST results showed that the Colombian tuber lesion samples clustered with those from the Venezuelan tuber lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Different potato cultivars show differences in susceptibility to root and tuber infection [21]. In Colombia it is well recognized that root galls are commonly formed on Sss -infected potato plants, and that tuber lesions caused by Sss are less frequently observed [22]. In most of the regions, where potato was introduced, both symptoms occur.…”
Section: Introductionmentioning
confidence: 99%
“…Root infection has been associated with disrupted root function and decreased water uptake, and with decreased plant growth and tuber yields (Falloon et al, , 2016Gilchrist, Soler, Merz, & Reynaldi, 2011;Hernandez Maldonado, Falloon, Butler, Conner, & Bulman, 2012;Shah et al, 2012). The impacts of root infection have also been examined in field studies utilizing a variety of methodologies and both naturally infested soils and field plots amended with pathogen inoculum.…”
Section: Discussionmentioning
confidence: 99%